Aproveitamento de resíduos e microscopia de força atômica em materiais biológicos - Santos, Ricardo Pires dos (2007)
This work describes some of the multidisciplinary researches accomplished in the Department of Physics of the Universidade Federal do Ceará (UFC), involving the use of residues involving the use of residues and atomic force microscopy (AFM) in the characterization of biological structures. Three residues were studied: cashew bagace, coal fly ashes, and Perna perna mussel shells. In the first, it was characterizated the ashes of the burned cashew’s peduncle. The composition analysis resulted in the KHCO3 and K2SO4 crystal phases, both important in the pharmaceutical industry and in the production of phosfatate fertilizers. In the second, it was used coal fly ashes ceramics from President Médici power plant as substrate for invertase immobilization. The invertase is responsible for the inverted sugar production. This application has direct use in the production of drinks, medications, and cosmetics. Finally in the third, it was studied the alterations in the composition, topography, and microhardness of the thermally treated Perna perna mussel shells. The mussel nacre (or madrepearl surface) has been used as biomaterial in the bony regeneration where are necessary sterilization processes (usually thermal). Like this, the importance of the establishment of mechanical, structural, and compositional stability regions during these processes. In the use of the atomic force microscope for study biological structures, it was given prominence the importance of this technique in the characterization of development Enterococcus faecalis biofilms. This biofilms are frequently found in clinical cases. In addition the nanostructural characterization of the sporopollenin of Ilex Paraguarinsis St. Hill pollen grains was performed. Sporopollenin is one of the toughest known materials which is degraded by oxidation but it is resistant to reduction.